Coronary tortuosity is associated with an elevated high-sensitivity C-reactive protein concentration and increased risk of ischemic stroke in hypertensive patients. Issue 4 (April 2018) - Li, Yang; Qadir Nawabi, Abdul; Feng, Yi; Ma, Genshan; Tong, Jiayi; Shen, Chengxing; Liu, Naifeng
Objective: The clinical implication of coronary tortuosity is unclear. The present study was conducted to determine the relationships between coronary tortuosity and the high-sensitivity C-reactive protein (hs-CRP) concentration and between coronary tortuosity and cerebrovascular accident in hypertensive patients without coronary artery disease. Methods: In total, 236 patients with normal coronary angiography findings were categorized into 3 different groups: control participants (n = 58), who had neither hypertension nor coronary tortuosity; patients with hypertension but no coronary tortuosity (H-NCT group, n = 93); and patients with both hypertension and coronary tortuosity (H-CT group, n = 85). The hs-CRP concentration was measured in every patient, and 168 hypertensive patients were followed up for at least 2 years to check for the development of cerebrovascular accident. Results: The hs-CRP concentration was significantly higher in the H-CT group than in the control and H-NCT groups (4.33 ± 3.15 vs. 1.52 ± 1.31 and 2.31 ± 2.09 mg/L, respectively). The incidence of lacunar infarction was higher in the H-CT than H-NCT group during the follow-up. Conclusions: Hypertensive patients with coronary tortuosity have a higher serum hs-CRP level concentration and have a higher incidence of lacunar infarction than hypertensive patients without coronary tortuosity.